Annual Plan 2009-10 Sectoral Plans Volume-II Government of Nagaland - Planning Commission (Planning Commission, 2009)
Set-up in 1968 as an Evaluation and monitoring and under the Planning & Co-ordination Department, the unit is now a full fledged Directorate with District Evaluation Offices in eight districts at Kohima, Mokokchung; Mon, Phek, Tuensung, Wokha, Zunheboto and Dimapur. Functions: The main function of the Evaluation Directorate is to undertake independent unbiased evaluation studies on implementation of the various schemes/programmes of the Government and suggest ways and means to bring about improvement in their formulation and execution. Through the two aspects (I) retrospective-assessment of the achievement of the programmes and (ii) prospective-what should be done to improve the programmes and through cost-benefit analysis the evaluation studies' Slid decision making and provide insight into the programmes.
Government of Nagaland Directorate of Evaluation